100 - ( 8 × 8 : 8 ) =
100 - ( 64 : 8 ) =
100 - 8 =
= 92
( 10 + 13 ) + ( 36 : 9 - 21 : 7 ) =
= 23 + ( 4 - 21 : 7 ) =
23 + ( 4 - 3 ) =
23 + 1 =
= 24
( 5 × 4 ) + ( 45 - 2 × 9 × 6 × 0 ) =
20 + ( 45 - 18 × 6 × 0 ) =
20 + ( 45 - 108 × 0 )=
20 + ( 45 - 0 ) =
20 + 45 =
= 65
164 + ( 100 - 9 : 9 - 5 × 10 ) =
164 + ( 100 - 1 - 5 × 10 ) =
164 + ( 100 - 1 - 50 ) =
164 + ( 99 - 50 ) =
164 + 49 =
= 213
5 × ( 10 : 10 × 10 ) + ( 8 × 3 - 23 ) =
5 × ( 1 × 10 )+ ( 24 - 23 ) =
5 × 10 + 1 =
50 + 1 =
= 51
48 + ( 103 - 100 ) × 9 + ( 24 : 3 × 0 ) =
48 + 3 × 9 + ( 8 × 0 ) =
48 + 3 × 9 + 0 =
48 + 27 + 0 =
= 75